Women’s prisons and women prisoners in the late Ottoman Empire (1840-1920): From invisibility to expendability - Sivri, Gizem. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2017., 2017)
In this thesis, I sketched a broad framework in the late Ottoman prison system and prisoners' institutional, legal, spatial problems and struggle with Ottoman approach towards women prisoners in terms of their gender roles, social ranks, fertilities, motherhood, and discriminative prison policy against them. Main aim of this thesis is to focus on special practical implementations and most importantly ignorance for women inmates even if they shared some of the same woeful conditions suffered by men, female prisoners were, in addi-tion, subject to abuses like rape, coercion, and discrimination in the Ottoman society just because of their feminity and vulnerability. In the light of these brief concepts, my main aspiration is to underline their expendable positions that women accused or inmates had been completely discriminated and stigmatized in the Ottoman modernization mentalities (in case of prison reform) in the Tanzimat (1839-1876), Hamidian (1876-1908) and Second Constitutional (1908-1920) Era. As an original perspective to depict female prisoners' positions diversed from the other criminals (male inmates) was derived from the negligence of them in the prisons with apparently varied practices that remained inside of the prisons. Furthermore, we evaluated their situation as disappeared figures of female inmates in Ottoman prison system. Briefly, I aimed at considering original roots of women prisoners' expendable roles within the concept of gendered criminality issue with the comparison between Ottoman women prisons (with counterparts of that in Near Eastern prisons) and European prisons implementations for the convicted women.
Keywords: Women prisoners -- Ottoman Empire, 1288-1918.